ANALISIS PERBANDINGAN TINGKAT KESEHATAN BANK BERDASARKAN RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS DAN CAPITAL (RGEC) PADA BANK SYARIAH (Studi pada Bank Syariah di Indonesia, Malaysia, United Arab Emirates, dan Kuwait Periode 2011-2015) - Khabibatur Rizkiyah; Suhadak Suhadak (Fakultas Ilmu Administrasi Universitas Brawijaya, 2017)
The business activity of a islamic bank could run well if its condition is in a healthy category, thus emerged PBI No.13/1/PBI/2011 to assess the health level of bank. The purpose of this study was comparing the health level of islamic banks in Indonesia with islamic banks in Malaysia, UAE and Kuwait. This research used three factors of RGEC they were risk profile using NPL and LDR, earnings using ROA, and capital performance using CAR at 13 banks in 4 countries. The results show on NPL ratio predicate Indonesia, Malaysia and Kuwait are